Factors Affecting Hydroponic Vegetable Purchase Decisions - Papilaya, Jan E; Massie, James DD; Tawas, Hendra N. (Research Parks Publishing LLC, 2022)
This study aims to assess the factors that influence the purchase decision of hydroponic vegetables at CV Hobata Farm Tobelo. This research is quantitative and uses associative research methods. The population in this study were hydroponic vegetable customers at CV Hobata Farm Tobelo. The sample used was 50 respondents. Methods of data collection using confirmatory factor analysis, multiple linear regression analysis, F test, t test, using the SPSS application program. The results showed that the factors of price perception, health awareness, brand image and quality simultaneously had a positive and significant effect on purchasing decisions for hydroponic vegetables at CV Hobata Farm Tobelo. Partially the price perception factor.